Design and experimental demonstration of a laser modulation system for future gravitational-wave detectors. (27th September 2019) - Yamamoto, Kohei; Kokeyama, Keiko; Michimura, Yuta; Enomoto, Yutaro; Nakano, Masayuki; Ge, Gui-Guo; Uehara, Tomoyuki; Somiya, Kentaro; Izumi, Kiwamu; Miyakawa, Osamu; Yamamoto, Takahiro; Yokozawa, Takaaki; et al.
Abstract: Detuning the signal-recycling cavity length from a cavity resonance significantly improves the quantum noise beyond the standard quantum limit, while there is no km-scale gravitational-wave (GW) detector successfully implemented the technique. The detuning technique is known to introduce great excess noise, and such noise can be reduced by a laser modulation system with two Mach–Zehnder interferometers in series. This modulation system, termed Mach–Zehnder modulator (MZM), also makes the control of the GW detector more robust by introducing the third modulation field which is non-resonant in any part of the main interferometer. On the other hand, mirror displacements of the Mach–Zehnder interferometers arise a new kind of noise source coupled to the GW signal port. In this paper, the displacement noise requirement of the MZM is derived, and also results of our proof-of-principle experiment is reported.